Pengaruh Penerapan Booklet Menu Seimbang Terhadap Peningkatan Berat Badan Bayi Usia 6-12 Bulan - Rosalinna Rosalinna; Apri Sulsitianingsih (Poltekkes Kemenkes Surakarta, 2019)
Background: In infancy, breast milk is the best food. Since the age of 6 months, babies begin to be given complementary breast milk food (MP-ASI). Giving the wrong MP-ASI will have an impact on nutritional disorders. The Karanganyar Regency in 2016 was 413 (0.8%), while the cases of under-fives were malnutrition which were found in 22 children. The aim of this study was to determine the effect of applying a balanced menu booklet to increasing infant weight at the age of 6-12 months in Karanganyar Regency. The method used in this study is the method in this study. Method: This research uses a quantitative method with a Quasy experiment in the form of pre-post test design. The sample in this study was 6-12 months Mother and Baby in Karanganyar District who had fulfilled the Inclusion and Exclusion criteria as many as 20 samples per group. Data analysis using paired and T independent T test. Results: The results of the control group study showed an average baby weight of 6.74 (0.63) kg to 6.86 (0.62) kg. Similarly, in the intervention group the average baby weight from 6.88 (0.44) kg to 7.25 (0.43) kg. The group given the booklet had a difference in the average increase in body weight higher (0.390 (0.151) kg) when compared to the group given only lectures (0.125 (0.121) kg). Conclusion: The statistical test results ρ value <0.001 which means there is an effect of the Implementation of a Balanced Menu Booklet Against the Increased Body Weight of 6-12 Months Babies in Karanganyar Regency. Health workers are advised to improve counseling skills to improve infant feeding practices that result in increased infant growth